“I hate English” A study on motivation. - Solano Gamboa, Madelein; Bernal, Andrea; Asesor (Corporación Universitaria Minuto de Dios, 2017)
Doing a study about the learning of English as a second language in a public school, it is possible to identify that students are not connected in their classes and they have lack of motivation. For this reason it is important to analyze the intrinsic factors, extrinsic and experiential that may be affecting the levels of motivation of each student. To give an explanation to this problem that is present in an educational context was necessary to measure the levels of motivation according to each of the factors mentioned above. For that reason this project works with a mixed research that has two phases, as quantitative as qualitative. First one helps to look if there is a problem and second one to find the reasons that cause of the lack of motivation of the students. Taking into account the foregoing, can be summarized that students have a certain degree of demotivation because of the lack of goals in the activities proposed by the teacher, where students have felt disoriented and disconnect easily. In addition to this it was possible to recognize that the experiences of the past come to have an impact on the motivation of students to study English, both positively and negatively. Finally, students do not see themselves as being influenced by their context; they have not contact to encourage their motivation in the learning of English. But this project makes them an aware about the importance of this language in their lives.
Keywords: language; Motivation; study English; Analyze the Intrinsic Factors; BILINGÜISMO; LENGUAJE Y LENGUAS; INGLÉS; LENGUAJE Y LENGUAS – GRAMÁTICA